Evaluation of the yield in sauce of five varieties of Solanum Lycopersicum (Nexo Revista Científica, 2022)
This work focuses on the evaluation of the performance of five tomato varieties for the transformation of sauce through the use of discarded tomatoes, the study is quantitative where a data collection of the varieties was made: Icsan (a), Nirvana (b ), Tysey (c), Butte (d) and Pony (e) all varieties were processed as sauce, constructing the description of the process used, and the material balance per variety, obtaining the following averages of sauce yield in Kg.: ( a) 1.23, (b) 1.23, (c) 0.58, (d) 1.07, (e) 1.13, which were analyzed with the completely random design that showed differences between the average weight of sauce, when applying the separation test of Duncan to varieties a, b, e, and d are similar in sauce weight yield, but significantly different from variety c, at a significance level of 0.05. The percentage amounts of juice obtained in the tomato varieties were (a) 90.5, (b) 87.6, (c) 75.2, (d) 90.5, (e) 91.4, and according to the amount of seeds and skin that the varieties in percentage based on fresh tomato weight were (a) 4.8, (b) 7.6, (c) 20, (d) 4.8, (e) 3.8.